Implementasi Good Governance Dan Perizinan Dalam Pemanfaatan Ruang Di Indonesia - Romi ' (Jurnal Ilmu Hukum, 2010)
The Spatial planning is government domain, becauseits related to the government as much as the basicneed of people who have been mandated by the con-stitution. There are at least two reasons that reinforcethese arguments, the first spatial planning is veryinfluential on the national investment climate. Andsecond, unintegrated spatial planning can lead toconflict horizontally on a practical level. The problemof its paper are how arrangement of spatial planningpermission in Indonesia and whether good gover-nance principles are accommodated in spatialplanning regulation in Indonesia. In practice,implementation of permission in the use of space inIndonesia has yet to be implemented to the maximum.The main factor cause is due to the unavailability ofregional spatial plan of local regulations (Perda RTRW)as the main parachute control utilization of space inthe area. Meanwhile, related to the implementation ofthe principles of good governance, at least the SpatialPlanning Act has been to accommodate the fourprinciples, namely principles of accountability,transparency principle, the principle of participationand the principle of legal certainty.